2009
DOI: 10.1007/s12195-009-0051-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulated Unfolding of von Willebrand Factor A Domains by Force

Abstract: The three tandem A domains (A1, A2, and A3) of von Willebrand factor (VWF) play critical roles for its functions. The A1 and A3 domains contain respective binding sites for platelet glycoprotein Ib (GPIb) and collagen. The A2 domain hosts a proteolytic site for the VWFcleavage enzyme A Disintegrin And Metalloprotease with a ThromboSpondin type 1 motifs 13 (ADAMTS-13). Previous studies suggested that shear flow assists the ADAMTS-13 cleavage of VWF by unfolding the A2 domain and thus exposing the cryptic proteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…One mode might be unfolding of the tertiary structure of the A2 domain (far right panel), as l d of approximately 50 nm is consistent with the contour length increase predicted for A2 unfolding. 27 The short length increase (l d ϳ 20 nm) might represent either partial unfolding of the A2 domain or uncoupling of the quaternary structure of the A1A2A3 tridomain by disrupting the domaindomain interactions (2 middle panels). Unfolding of A1 or A3 is improbable because each domain contains a disulfide bond between cystines at the N-and C-termini that makes it strongly resistant to unfolding.…”
mentioning
confidence: 99%
“…One mode might be unfolding of the tertiary structure of the A2 domain (far right panel), as l d of approximately 50 nm is consistent with the contour length increase predicted for A2 unfolding. 27 The short length increase (l d ϳ 20 nm) might represent either partial unfolding of the A2 domain or uncoupling of the quaternary structure of the A1A2A3 tridomain by disrupting the domaindomain interactions (2 middle panels). Unfolding of A1 or A3 is improbable because each domain contains a disulfide bond between cystines at the N-and C-termini that makes it strongly resistant to unfolding.…”
mentioning
confidence: 99%
“…Recent molecular dynamics simulations 17,18 and studies using optical tweezers 19 have suggested that the A2 domain unfolds progressively from its C-terminus; the ␣6-helix is peeled off first, followed by the ␤6 and ␣5-helix. 17,18 We propose that the vicinal disulfide bond primarily influences the initial uncoupling of the ␣6-helix and therefore directly modulates the exposure of the high-affinity ADAMTS13-binding site. Thereafter, a second unfolding step is required for the detachment of the ␤5 and ␣4-less loop and exposure of the cleavage site in the ␤4 strand, as A2-⌬CC is cleaved inefficiently without denaturant.…”
mentioning
confidence: 99%
“…This is similar to the first level exposure observed in the unfolding of A2 by force. 5 Then the SASA of the sidechains was elevated up to~150 Å 2 while the SASA of the backbones increased up to~25 Å 2 . This is similar to the second level exposure observed in the unfolding of A2 by force.…”
Section: Exposure Of the Proteolytic Site Of A2mentioning
confidence: 99%
“…12,25 A suggested mechanism for the enhancing effect is that shear flow or denaturants unfold the A2 domain and expose the proteolytic site for cleavage by ADAMTS-13. 1 In our previous atomic force microscopy (AFM) experiments 29 and molecular dynamics (MD) simulations, 5 we have demonstrated that tensile force can unfold the VWF A2 domain and expose its cryptic proteolytic site. Here we studied the thermal unfolding of the VWF A domains with MD simulations, which were performed at high temperature to accelerate conformational sampling.…”
Section: Introductionmentioning
confidence: 95%